Alternations of interhemispheric functional connectivity in patients with acute acquired concomitant esotropia: a resting state fMRI study using voxel-mirrored homotopic connectivity - Jiayu Chen; Jie Hao; Jiawen Liu; Huijian Li; Zhaojun Meng; Jing Fu (Frontiers in Neuroscience)
PurposeTo investigate the changes in cerebral hemispheric functional connections in patients with acute acquired concomitant esotropia (AACE) and their relationship with clinical manifestations, utilizing voxel-mirrored homotopic connectivity (VMHC).MethodsA prospective, observational study was conducted involving 32 AACE patients and 31 age-, sex-, and education-matched healthy controls (HC). The resting-state functional magnetic resonance imaging (rs-fMRI) signals, binocular vision function, and psychometric scale scores were collected rs-fMRI data and structural image data were analyzed for VMHC, and a two-sample t-test was used to analyze the differences in VMHC between groups. Spearman correlation analysis evaluated the relationship between fMRI indicators and clinical features.ResultsThere was no statistical difference between the two groups concerning sex, age, height and weight. VMHC levels in the superior frontal gyrus and anterior cingulate were significantly lower in the AACE group (p < 0.05). In the AACE group, the VMHC values of the left caudate positively correlated with near vision work duration (r = 0.381, p = 0.034), the deviation angles at near (r = 0.428, p = 0.015) and at distance (r = 0.416, p = 0.018). The VMHC values in the bilateral olfactory cortex also positively correlated with the near vision work duration (Right: r = 0.389, p = 0.031; Left: r = 0.372, p = 0.039) while Beck Depression Inventory (BDI) scores negatively correlated with the VMHC values of the left olfactory cortex (r = −0.359, p = 0.048).ConclusionThe dysfunction of the medial frontal gyrus and anterior cingulate gyrus is the underlying neuropathological mechanism of AACE, and these dysfunctions may be related to poor eye habits and the severity of deviation.